2016
DOI: 10.4103/0974-7796.190815
|View full text |Cite
|
Sign up to set email alerts
|

Holmium laser transurethral resection of bladder tumor: Our experience

Abstract: Purpose:To compare the safety and efficiency of conventional monopolar and holmium laser en bloc transurethral resection of bladder tumor (CM-TURBT and HoL-EBRBT) while managing primary nonmuscle-invasive bladder cancer.Materials and Methods:From January 2012 to October 2015, fifty patients with primary nonmuscle-invasive bladder cancer underwent endoscopic surgery. Among them, 27 patients underwent CM-TURBT and 23 patients underwent HoL-EBRBT. Clinical data, included preoperative, operative, and postoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 20 publications
4
44
0
3
Order By: Relevance
“…In the next study on 27 patients after mTURB and 23 patients after HoLRBT, the authors showed that there were no significant differences in operation time and recurrence rates between the two groups. The HoLRBT group had lower intraoperative and postoperative complication rates, but there were no significant differences in the transfusion rates and occurrence of urethral strictures [45].…”
Section: En Bloc Using a Holmium Lasermentioning
confidence: 76%
“…In the next study on 27 patients after mTURB and 23 patients after HoLRBT, the authors showed that there were no significant differences in operation time and recurrence rates between the two groups. The HoLRBT group had lower intraoperative and postoperative complication rates, but there were no significant differences in the transfusion rates and occurrence of urethral strictures [45].…”
Section: En Bloc Using a Holmium Lasermentioning
confidence: 76%
“…Fig.1 summarized the inclusion process. We performed intravesical chemotherapy or Bacille Calmette-Guerin BCG for postoperative patients, mitomycin was used in 5 studies [8,9,[15][16][17], epirubicin was used in 7 studies [6,7,10,12,14,23,24], pirarubicin was used in 5 studies [13,18,[20][21][22], BCG was used in 1 study [11] and BCG combined epirubicin [19] was used in 1 study.…”
Section: Eligible Studies and Characteristicsmentioning
confidence: 99%
“…Furthermore, 11 non-randomised studies [6,8,9,11,[15][16][17][20][21][22]24] were considered of high quality due to the score ≥7 stars ( Table 2). While there was a high heterogeneity in all comparisons, which may come from the patient demographics, difference in types of surgery and tumor characteristics.…”
Section: Quality Assessment Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Podejmowane są próby leczenia nienaciekających raków pęcherza moczowego (non-muscle-invasive bladder tumour -NMIBC) z użyciem lasera holmowego i tulowego, aczkolwiek zgodnie z obowiązującymi wytycznymi międzynarodowych towarzystw urologicznych przezcewkowa elektroresekcja guza pęcherza moczowego (transurethral resection of bladder tumour -TURBT) wciąż pozostaje tzw. złotym standardem [4][5][6]. Opublikowano również prace dotyczące zastosowania lasera holmowego i diodowego w częściowej nefrektomii, należy jednak uznawać to wciąż za metodę eksperymentalną, której skuteczność wymaga potwierdzenia w dalszych badaniach [7][8][9].…”
Section: Rodzaje I Charakterystyka Laserów Stosowanych W Urologiiunclassified